Metodyka oceny ryzyka zasobów energetycznych wiatru - Soliński, Bartosz (Wind Energy Resources Risk Evaluation Methodology, 2007)
The methodology of wind energy resources risk evaluation presented in the paper was based on the probabilistic distribution function analysis of wind velocity random variable V-f (v;ΘA, Θk)- which parameters ΘA, Θk, characterize the amounts of these resources. The estimators of these distribution functions parameters Θi1,....,Θit are being treated as random variables in homogeneous periods because they are changing during following periods of time. Thus, they significantly influence on changeability of these resources amounts. Taking into consideration these parameters changeability f [v; f (ΘA), f (Θk)] allows to evaluate the wind energy resources, as well the risk connected with application of resources representative for long period of time.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 560-568